Stainless steel mesh oil-water separation material as well as preparation method and application thereof
After etching the stainless steel mesh in a solution containing sodium hydroxide and ammonium persulfate, it is treated in the oxalic acid solution to form iron oxalate pentahydrate precipitation, which improves the oleophobicity and hydrophilicity of the stainless steel mesh, and solves the oil and water in the prior art The problem of poor separation effect achieves efficient and low-cost oil-water separation effect.
Patent Information
- Application Number
- CN202411415037.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing superhydrophobic copper mesh has poor effect in oil-water separation, and the preparation process is complex and costly.
The stainless steel mesh is soaked in a mixed solution containing sodium hydroxide and ammonium persulfate, and then treated in the oxalic acid solution to form iron oxalate pentahydrate precipitate, which improves the oleophobicity and hydrophilicity of the stainless steel mesh, thereby preparing efficient Stainless steel mesh oil-water separation material.
It realizes rapid and efficient separation of oil-water separation materials, with separation efficiency of more than 99.5%, fluxes above 5.0×104 liters per square meter per hour, and low cost, suitable for industrial production.
Smart Images

Figure CN119258594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite material, in particular to a stainless steel mesh oil-water separation material and a preparation method and application thereof. Background Art
[0002] Oil-water separation technology is of great significance in treating oily wastewater and leaked crude oil. The most common oil-water separation technology is membrane separation technology, which uses super-hydrophobic materials to efficiently intercept water or oil to achieve oil-water separation. However, the current preparation process of super-hydrophobic materials is complex and costly.
[0003] In the prior art, there is a solution for oil-water separation by using a super-hydrophobic copper mesh. However, the oil-water separation effect of the super-hydrophobic copper mesh needs to be improved. Summary of the invention
[0004] In order to solve the problem that the oil-water separation material in the prior art has a poor oil-water separation effect, the present invention provides a stainless steel mesh oil-water separation material and a preparation method and application thereof.
[0005] The first aspect of the present invention provides a method for preparing a stainless steel mesh oil-water separation material, which comprises the following steps:
[0006] The stainless steel mesh is immersed in a mixed solution containing sodium hydroxide and ammonium persulfate;
[0007] Taking out the stainless steel mesh and soaking it in an oxalic acid solution to obtain a stainless steel mesh oil-water separation material;
[0008] Wherein, in the mixed solution containing sodium hydroxide and ammonium persulfate, the mass concentration of sodium hydroxide is 3% to 20%, the mass concentration of ammonium persulfate is 1% to 6%; the mass concentration of the oxalic acid solution is 0.2% to 5%.
[0009] A second aspect of the present invention provides a stainless steel mesh oil-water separation material, which is obtained by the preparation method of the stainless steel mesh oil-water separation material.
[0010] The third aspect of the present invention provides the use of the stainless steel mesh oil-water separation material in oil-water separation.
[0011] A fourth aspect of the present invention provides an oil-water separation method, which comprises the following steps:
[0012] Placing the oil-water mixture on one side of the stainless steel mesh oil-water separation material;
[0013] The water in the oil-water mixture is made to pass through the stainless steel mesh oil-water separation material under the action of driving force.
[0014] The technical solution of the embodiment of the present invention has the following beneficial effects:
[0015] (1) treating the stainless steel mesh with a mixed solution containing sodium hydroxide and ammonium persulfate and an oxalic acid solution in sequence, so that iron oxalate pentahydrate precipitates are formed on the surface of the stainless steel mesh, thereby increasing the oleophobicity and hydrophilicity of the stainless steel mesh oil-water separation material;
[0016] (2) Stainless steel mesh oil-water separation material can quickly and efficiently separate wastewater containing refrigeration oil, toluene, petroleum ether, paraffin oil, ether, etc. The separation efficiency can reach more than 99.5%, and the separation flux can be higher than 5.0×10 4 Liters per square meter per hour;
[0017] (3) Stainless steel mesh oil-water separation material has low cost and simple preparation method, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscopy (SEM) image of the untreated stainless steel mesh.
[0019] Figure 2 This is a scanning electron microscope image (SEM) of the stainless steel mesh oil-water separation material in Example 9 of the present invention.
[0020] Figure 3 This is the infrared spectrum of the stainless steel mesh oil-water separation material in Example 9 of the present invention.
[0021] Figure 4 This is a surface energy spectrum analysis diagram of the stainless steel mesh oil-water separation material in Example 9 of the present invention.
[0022] Figure 5 It is a contact angle analysis diagram of the untreated stainless steel mesh and the stainless steel mesh oil-water separation material in Example 9 of the present invention.
[0023] Figure 6 This is a contact angle analysis diagram of the stainless steel mesh oil-water separation material in Examples 13, 15, 18, and 22 of the present invention.
[0024] Figure 7 These are actual photographs of the oil-water separators in Examples 23 to 27 of the present invention.
[0025] Figure 8 This is a graph showing the oil-water separation experimental results of the stainless steel mesh oil-water separation material in Examples 23 to 27 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] The first aspect of the present invention provides a method for preparing a stainless steel mesh oil-water separation material, which comprises the following steps:
[0028] The stainless steel mesh is immersed in a mixed solution containing sodium hydroxide and ammonium persulfate;
[0029] Taking out the stainless steel mesh and soaking it in an oxalic acid solution to obtain a stainless steel mesh oil-water separation material;
[0030] Wherein, in the mixed solution containing sodium hydroxide and ammonium persulfate, the mass concentration of sodium hydroxide is 3% to 20%, the mass concentration of ammonium persulfate is 1% to 6%; the mass concentration of the oxalic acid solution is 0.2% to 5%.
[0031] In the specific operation, sodium hydroxide and ammonium persulfate can be dissolved in a solvent, and then the stainless steel mesh can be completely immersed in a mixed solution containing sodium hydroxide and ammonium persulfate for etching. After the etching is completed, the etched stainless steel mesh is immersed in an oxalic acid solution for treatment, and finally dried to obtain a stainless steel mesh oil-water separation material. Etching the stainless steel mesh with a mixed solution containing sodium hydroxide and ammonium persulfate can increase the roughness and surface area of the stainless steel mesh; after the etched stainless steel mesh is treated in an oxalic acid solution, the oleophobicity and hydrophilicity of the stainless steel mesh can be greatly improved; the obtained stainless steel mesh oil-water separation material has excellent oil-water separation performance and can quickly and efficiently separate oily wastewater.
[0032] In some embodiments, in the mixed solution containing sodium hydroxide and ammonium persulfate, the mass ratio of ammonium persulfate to sodium hydroxide is 20:80 to 40:60. Preferably, the mass ratio of ammonium persulfate to sodium hydroxide is 20:80 to 30:70.
[0033] In some embodiments, in the mixed solution containing sodium hydroxide and ammonium persulfate, the mass concentration of sodium hydroxide is 8% to 15%, and the mass concentration of ammonium persulfate is 3% to 5%. Preferably, in the mixed solution containing sodium hydroxide and ammonium persulfate, the mass concentration of sodium hydroxide is 12%, and the mass concentration of ammonium persulfate is 3.5%.
[0034] In some embodiments, the mass concentration of the oxalic acid solution is 0.5% to 3%. Preferably, the mass concentration of the oxalic acid solution is 1%.
[0035] In some embodiments, the pore size of the stainless steel mesh is 800-3000 mesh. Preferably, the pore size of the stainless steel mesh is 1400-2000 mesh.
[0036] In some embodiments, the stainless steel mesh is immersed in a mixed solution containing sodium hydroxide and ammonium persulfate at 20 to 70° C. for 1 to 72 hours. Preferably, the stainless steel mesh is immersed in a mixed solution containing sodium hydroxide and ammonium persulfate at 40 to 60° C. for 18 to 36 hours.
[0037] In some embodiments, the stainless steel mesh is taken out and immersed in an oxalic acid solution at 20 to 70° C. for 1 to 10 hours to obtain a stainless steel mesh oil-water separation material.
[0038] In some embodiments, the solvents of the mixed solution containing sodium hydroxide and ammonium persulfate and the oxalic acid solution are one or more of water, ethanol, dimethylformamide, and dimethylacetamide. Preferably, the solvents of the mixed solution containing sodium hydroxide and ammonium persulfate and the oxalic acid solution are one or two of water and ethanol.
[0039] In some embodiments, the stainless steel mesh is an industrial grade stainless steel mesh or a non-industrial grade stainless steel mesh. Preferably, the stainless steel mesh is an industrial grade stainless steel mesh.
[0040] In some embodiments, the sodium hydroxide is industrial grade sodium hydroxide or non-industrial grade sodium hydroxide. Preferably, the sodium hydroxide is industrial grade sodium hydroxide.
[0041] In some embodiments, the ammonium persulfate is industrial grade ammonium persulfate or non-industrial grade ammonium persulfate. Preferably, the ammonium persulfate is industrial grade ammonium persulfate.
[0042] In some embodiments, the oxalic acid is industrial grade oxalic acid or non-industrial grade oxalic acid. Preferably, the oxalic acid is industrial grade oxalic acid.
[0043] It should be noted that the stainless steel mesh, sodium hydroxide, ammonium persulfate and oxalic acid are commonly used materials in the art and are not particularly limited.
[0044] A second aspect of the present invention provides a stainless steel mesh oil-water separation material, which is obtained by the preparation method of the stainless steel mesh oil-water separation material.
[0045] The third aspect of the present invention provides the use of the stainless steel mesh oil-water separation material in oil-water separation.
[0046] A fourth aspect of the present invention provides an oil-water separation method, which comprises the following steps:
[0047] Placing the oil-water mixture on one side of the stainless steel mesh oil-water separation material;
[0048] The water in the oil-water mixture is made to pass through the stainless steel mesh oil-water separation material under the action of driving force.
[0049] In some embodiments, the oil in the oil-water mixture is one or more of motor oil, toluene, petroleum ether, paraffin oil, and ether.
[0050] In some embodiments, the driving force is gravity or pressure. For example, an oil-water mixture is placed on the stainless steel mesh oil-water separation material, so that the water in the oil-water mixture passes through the stainless steel mesh oil-water separation material under the action of the oil-water mixture's own gravity. For another example, an oil-water mixture is placed on one side of the stainless steel mesh oil-water separation material, and pressure is applied to the oil-water mixture, so that the water in the oil-water mixture passes through the stainless steel mesh oil-water separation material.
[0051] Some typical embodiments are described below. In the following embodiments, the raw materials used are all commercially available products.
[0052] Example 1 to Example 12
[0053] Fully dissolve 3g of sodium hydroxide and 1g of ammonium persulfate in 96g of water to obtain a mixed solution; immerse a stainless steel mesh with a pore size of 1400 mesh in the mixed solution for etching at a temperature of 40°C for 24h to obtain an etched stainless steel mesh. Fully dissolve 1g of oxalic acid in 99g of water to obtain an oxalic acid solution; immerse the etched stainless steel mesh in the oxalic acid solution for 4h at a soaking temperature of 40°C to obtain a stainless steel mesh oil-water separation material.
[0054] By changing parameters such as the amount of sodium hydroxide, the amount of ammonium persulfate, the etching time, the amount of oxalic acid, and the oxalic acid treatment time, different stainless steel mesh oil-water separation materials can be obtained by the same steps.
[0055] The specific parameters of Examples 1 to 12 are shown in Table 1.
[0056] Table 1 Specific parameters of Examples 1 to 12
[0057]
[0058] The surface of the untreated stainless steel mesh and the stainless steel mesh oil-water separation material obtained in Example 9 were analyzed using a scanning electron microscope (SEM). The analysis results of the untreated stainless steel mesh are as follows: Figure 1 As shown, it can be seen that the surface of the untreated stainless steel mesh is relatively smooth overall. The analysis results of the stainless steel mesh oil-water separation material obtained in Example 9 are as follows Figure 2As shown, it can be seen that after etching with a mixed solution containing sodium hydroxide and ammonium persulfate and treated with oxalic acid, the surface of the stainless steel mainly presents an irregular polygonal structure with obvious boundaries between the polygons, and the surface of the irregular polygon presents an uneven rough structure. In Examples 1 to 12, as the composition of sodium hydroxide and ammonium persulfate changes, the roughness of the overall morphology of the obtained stainless steel mesh increases with the increase of the concentration of the two.
[0059] The stainless steel mesh oil-water separation material obtained in Example 9 was characterized by infrared spectroscopy (FTIR). The test results are as follows: Figure 3 In the infrared spectrum, 1700cm -1 The characteristic absorption peak of carbonyl (C=O) is 3450cm -1 The absorption peak at is the hydroxyl absorption peak. Figure 3 From the analysis, it can be found that the carbonyl and hydroxyl content of the stainless steel mesh increased after etching and oxalic acid treatment, indicating that the stainless steel mesh has more polar groups on the surface after etching and oxalic acid treatment. The main process of introducing carbonyl and hydroxyl groups into the stainless steel mesh is as follows:
[0060] The stainless steel mesh is first etched in an ammonium persulfate solution containing sodium hydroxide to form black iron oxide hydroxide (FeO(OH)) on the surface. The specific process is as follows:
[0061] Fe+2NaOH+(NH4)2S2O4→FeO(OH)↓+Na2SO4+NH3↑+H2O;
[0062] Ferric hydroxide reacts with oxalic acid to form ferric oxalate precipitate (Fe2(C2O4)3). The reaction process is:
[0063] FeO(OH)+H2C2O4→Fe2(C2O4)3↓+H2O.
[0064] Ferrous oxalate is attached to the surface of the stainless steel mesh in the form of precipitation, and in the presence of water, ferrous oxalate forms a pentahydrate ferrous oxalate precipitate (Fe2(C2O4)3·5H2O). The surface of the precipitate has high hydrophilicity.
[0065] The stainless steel mesh oil-water separation material obtained in Example 9 was subjected to X-ray photoelectron spectroscopy (XPS) analysis. The results were as follows: Figure 4 As shown. Figure 4 It can be seen that the energy spectrum of the treated stainless steel mesh shows strong C=O bond, CC bond, and C-OH energy spectrum signals, which indicates that a large number of polar groups other than metal elements are formed on the surface of the stainless steel, the surface of the stainless steel mesh is successfully etched, and a large amount of Fe2(C2O4)3·5H2O is formed.
[0066] The contact angle test was performed on the untreated stainless steel mesh and the stainless steel mesh oil-water separation material obtained in Example 9. The results are as follows: Figure 5 As shown. On the surface of the untreated stainless steel mesh, water can stably exist in the form of hemispherical droplets, and the droplets do not change significantly after being placed for 0.5 hours. Water drops are dropped onto the surface of the stainless steel mesh oil-water separation material obtained in Example 9. Within 2 seconds, the droplets penetrate into the surface and cannot form stable droplets. And the underwater oil contact angle of the stainless steel mesh oil-water separation material obtained in Example 9 can reach 161°. Its high oleophobicity mainly comes from two aspects. First, a large amount of Fe2(C2O4)3·5H2O precipitates are formed on the surface of the stainless steel mesh after oxalic acid treatment. The accumulation of the precipitates increases the roughness of the stainless steel surface, forming a lotus leaf effect and increasing the oleophobicity. Second, Fe2(C2O4)3·5H2O contains a large amount of crystalline water, which can form a hydration layer with free water molecules, further increasing the oleophobicity of the stainless steel.
[0067] Example 13 to Example 17
[0068] Dissolve 12g of sodium hydroxide and 3.5g of ammonium persulfate in 84.5g of water to prepare a mixed solution of 12% sodium hydroxide solution and 3.5% ammonium persulfate. Place the stainless steel mesh in the mixed solution and fully etch it at 40°C for 24 hours to obtain an etched stainless steel mesh. Then dissolve 0.2g of oxalic acid in 99.8g of water to obtain an oxalic acid solution; soak the etched stainless steel mesh in the oxalic acid solution at 40°C for 4 hours to obtain a stainless steel mesh oil-water separation material.
[0069] A series of stainless steel mesh oil-water separation materials can be obtained by changing the concentration of oxalic acid solution, and their specific parameters are shown in Table 2.
[0070] Table 2 Specific parameters of Examples 13 to 17
[0071]
[0072] The stainless steel mesh oil-water separation materials obtained in Examples 13 to 17 were analyzed by SEM. The surface of the stainless steel mesh oil-water separation materials showed a rough structure as a whole. As the amount of oxalic acid increased, the roughness of the surface of the stainless steel mesh oil-water separation materials first increased and then decreased. Among them, the roughness was the highest when the oxalic acid concentration was 1%.
[0073] The stainless steel mesh oil-water separation materials obtained in Examples 13 to 17 were characterized by infrared spectroscopy. It was found that as the concentration of oxalic acid increased, the obtained stainless steel mesh oil-water separation materials had a higher relative humidity at 1700 cm -1 、3450cm -1The absorption peak at also gradually becomes stronger, indicating that with the increase of oxalic acid concentration, the number of polar groups on the surface of the stainless steel mesh increases.
[0074] XPS characterization was performed on the stainless steel mesh oil-water separation materials obtained in Examples 13 to 17, and it was found that as the content of oxalic acid in the solution increased, the signals of the C=O bond, CC bond, and C-OH showed an increasing trend.
[0075] The underwater oil contact angle test of the stainless steel mesh oil-water separation material obtained in Examples 13 to 17 showed that the underwater oil contact angle varied in the range of 155° to 161°. Figure 6 As shown, the contact angle is 155°. The underwater oil contact angle of the stainless steel mesh oil-water separation material of Example 15 is as follows Figure 6 As shown, the contact angle is 159°.
[0076] Example 18 to Example 22
[0077] 12g of sodium hydroxide and 3.5g of ammonium persulfate were dissolved in 84.5g of water to prepare a mixed solution of 12% sodium hydroxide solution and 3.5% ammonium persulfate. The stainless steel mesh was placed in the mixed solution and fully etched at 40°C for 24 hours to obtain an etched stainless steel mesh. The etched stainless steel mesh was then treated in a 1% oxalic acid solution at 40°C for 1 hour to obtain a stainless steel mesh oil-water separation material.
[0078] A series of stainless steel mesh oil-water separation materials can be obtained by changing the treatment time of oxalic acid solution, and their specific parameters are shown in Table 3.
[0079] Table 3 Specific parameters of Examples 18 to 22
[0080]
[0081] The stainless steel mesh oil-water separation materials obtained in Examples 18 to 22 were analyzed using SEM. The surface of the stainless steel mesh oil-water separation materials showed a rough structure as a whole. As the treatment time with oxalic acid solution increased, the roughness first increased. After 4 hours of treatment, the roughness remained basically unchanged.
[0082] The stainless steel mesh oil-water separation materials obtained in Examples 18 to 22 were characterized by infrared spectroscopy. It was found that as the oxalic acid solution treatment time increased, the obtained stainless steel mesh had a -1 、3450cm -1 The absorption peak at also first increases and then stops changing.
[0083] XPS characterization was performed on the stainless steel mesh oil-water separation materials obtained in Examples 18 to 22, and it was found that as the treatment time of the oxalic acid solution in the solution increased, the signals of the C=O bond, CC bond, and C-OH showed an increasing trend.
[0084] The underwater oil contact angle of the stainless steel mesh oil-water separation material obtained in Examples 18 to 22 was characterized, and it was found that the contact angle first increased; when treated with oxalic acid for 4 hours, the contact angle was the largest, reaching 161° (Example 9); as the treatment time continued to increase, the contact angle showed a downward trend. The underwater oil contact angle photo of the stainless steel mesh oil-water separation material in Example 18 is shown in Figure 1. Figure 6 As shown, the contact angle is 157°; the underwater oil contact angle photo of the stainless steel mesh oil-water separation material of Example 22 is shown Figure 6 As shown, the contact angle is 159°
[0085] Example 23 to Example 27
[0086] The stainless steel mesh oil-water separation material prepared in Example 9 was cut into a size of 2 cm×2 cm to conduct an oil-water separation experiment. First, the refrigeration oil was mixed with water in a ratio of 1:9 to obtain an oil-water mixture; the stainless steel mesh oil-water separation material prepared in Example 9 was used as a separation membrane and installed on a separator. The structure of the separator is as follows: Figure 7 100 mL of oil-water mixture was poured into the separator from the top to conduct the oil-water separation experiment. The water flux was calculated using formula 1 and the oil-water separation efficiency was calculated using formula 2.
[0087] Separation flux (Flux) = V / St(1)
[0088] Among them, V represents the volume of water passing through the separator, in liters; S represents the effective cross-sectional area of the oil-water separation material during the separation process, in square meters; t represents the time of oil-water separation, in hours.
[0089] Separation efficiency (SE) % = (1-C f / C0)(2)
[0090] Among them, C f represents the weight of the oil after separation, and C0 represents the weight of the oil before separation.
[0091] The above separation experiment was repeated 10 times, and the average separation flux and separation efficiency were calculated.
[0092] By changing different types of oil for separation experiments, a series of different separation flux and separation efficiency data can be obtained, and the specific parameters are shown in Table 4.
[0093] Table 4 Specific parameters of different oil-water mixtures
[0094] Example Oil Type Oil dosage (mL) Water consumption (mL) Embodiment 23 Refrigeration oil 10 90 Embodiment 24 Toluene 10 90 Embodiment 25 Petroleum ether 10 90 Embodiment 26 Paraffin oil 10 90 Embodiment 27 Ether 10 90
[0095] The separation flux and separation efficiency of various oil-water mixtures are as follows: Figure 8 The separation flux varies with the type of oil. The average flux of paraffin oil and refrigeration oil can be higher than 5.0×10 4 liters per square meter per hour, and the average water flux of toluene is also higher than 2.7×10 4 Liters per square meter per hour. Although the separation fluxes vary greatly, the separation efficiencies of the above five oil-water mixtures are all higher than 99.5%.
[0096] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a stainless steel mesh oil-water separation material, characterized in that: The following steps are involved: The stainless steel mesh is immersed in a mixed solution containing sodium hydroxide and ammonium persulfate; Taking out the stainless steel mesh and soaking it in an oxalic acid solution to obtain a stainless steel mesh oil-water separation material; Wherein, in the mixed solution containing sodium hydroxide and ammonium persulfate, the mass concentration of sodium hydroxide is 3% to 20%, the mass concentration of ammonium persulfate is 1% to 6%; the mass concentration of the oxalic acid solution is 0.2% to 5%.
2. The method according to claim 1, characterized in that In the mixed solution containing sodium hydroxide and ammonium persulfate, the mass concentration of sodium hydroxide is 8% to 15%, and the mass concentration of ammonium persulfate is 3% to 5%.
3. The method according to claim 1, characterized in that The mass concentration of the oxalic acid solution is 0.5% to 3%.
4. The method according to claim 1, characterized in that: Under the condition of 20-70°C, the stainless steel mesh is immersed in a mixed solution containing sodium hydroxide and ammonium persulfate for 1-72 hours.
5. The method according to claim 1, characterized in that: The stainless steel mesh is taken out and immersed in an oxalic acid solution at 20 to 70° C. for 1 to 10 hours to obtain a stainless steel mesh oil-water separation material.
6. The method according to claim 1, characterized in that The solvents of the mixed solution containing sodium hydroxide and ammonium persulfate and the oxalic acid solution are respectively one or more of water, ethanol, dimethylformamide and dimethylacetamide.
7. A stainless steel mesh oil-water separation material, characterized in that: The oil-water separation material is obtained by the preparation method of the stainless steel mesh described in any one of claims 1 to 6.
8. Use of the stainless steel mesh oil-water separation material according to claim 7 in oil-water separation.
9. An oil-water separation method, characterized in that: The following steps are involved: Placing the oil-water mixture on one side of the stainless steel mesh oil-water separation material of claim 7; The water in the oil-water mixture is made to pass through the stainless steel mesh under the action of a driving force.
10. The method according to claim 9, characterized in that The oil in the oil-water mixture is one or more of engine oil, toluene, petroleum ether, paraffin oil and ether.
Citation Information
Patent Citations
Production method of superhydrophobic / superlipophilic high-efficiency oil-water separation membrane
CN108771982A
Oil-water separation membrane and preparation method and application thereof
CN112675576A
Method for forming oxalic acid coating film with superior adhesiveness
JP2005194584A